2018
DOI: 10.1007/s00125-018-4636-9
|View full text |Cite
|
Sign up to set email alerts
|

The novel adipokine WISP1 associates with insulin resistance and impairs insulin action in human myotubes and mouse hepatocytes

Abstract: Circulating WISP1 levels and WISP1 expression in VAT are increased in obesity independent of glycaemic status. Furthermore, WISP1 impaired insulin signalling in muscle and liver cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 36 publications
3
47
0
1
Order By: Relevance
“…Serum concentration of the adipokine is elevated in obesity, irrespective of glycemia or insulin resistance status . This observation was reinforced in a different study, where WISP1 levels were found elevated in obese men irrespective of glycemic status compared with nonobese men . Additionally, the group showed that insulin signaling was impaired when hepatocytes were incubated with WISP1 due to inhibition of insulin receptor phosphorylation, other downstream regulators, and suppression of glycogenesis as well as gluconeogenesis.…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 89%
“…Serum concentration of the adipokine is elevated in obesity, irrespective of glycemia or insulin resistance status . This observation was reinforced in a different study, where WISP1 levels were found elevated in obese men irrespective of glycemic status compared with nonobese men . Additionally, the group showed that insulin signaling was impaired when hepatocytes were incubated with WISP1 due to inhibition of insulin receptor phosphorylation, other downstream regulators, and suppression of glycogenesis as well as gluconeogenesis.…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 89%
“…In insulin-sensitive tissue, WISP-1 decreases the phosphorylation of insulin receptor and protein kinase B (akt). As a consequence, glycogen synthesis is reduced in myotubes, and gluconeogenic genes are upregulated in hepatocytes 17 . Accordingly, we observed significant correlations of serum WISP-1 level with fasting insulin, HOMA-IR, waist circumference, BMI, and body fat percentage in a cross-sectional analysis ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Übersicht über diese Zusammenhänge findet sich bei Fasshauer et al [3]. In einer aktuellen Studie haben Hörbelt et al ein weiteres Adipokin (WISP1) identifiziert, das eine Insulinresistenz von Muskelzellen bewirken kann [4].…”
Section: Merkeunclassified